The Practicality of Popular Scientific Books based on the Diversity of Mangrove Shrubs in Tabanio Village - Chitania Millianton; Yudi Firmanul Arifin; Dharmono Dharmono (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
The development of a popular scientific book that is developed based on the local potential of a region is one solution that can be used to overcome problems that often arise such as a lack of student reading interest due to boring teaching materials and learning medifications in the Low Plant Botany course, especially in several studies of shrub diversity that require students to make direct observations. This development research aims to describe the practicality of the popular scientific book prototype entitled